Analysis of Arabic Language Learning Achievement of 7th Grade Students of Muhammadiyah 3 Junior High School Yogyakarta - Novela Gibyana Widayat; Ana Taqwa Wati; Erma Febriani (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2025)
This research is motivated by the number of Arabic language scores of 7th grade students of Muhammadiyah 3 Junior High School Yogyakarta in the academic year 2023/2024, which remain below the Minimum Mastery Criteria (KKM) index of 75. This study aims to analyze the achievement of Arabic learning outcomes of 7th grade students of Muhammadiyah 3 Junior High School Yogyakarta compared with the Arabic achievement index of Muhammadiyah Junior High School in Yogyakarta. This study uses a quantitative descriptive research method, and the data collection technique uses documentation. The sample in this study is 7th grade students of Muhammadiyah 3 Junior High School Yogyakarta 2023/2024 period, which totals thirty students. In this study, the researcher uses a random sampling method, and the data analysis technique used is one sample t-test. Based on the data collected and tested using SPSS version 25, it shows that the independent sample t-test produces a T-Count value of -12,961< 1.984217. Most students have not reached the Minimum Completion Criteria (KKM) set at 75, so it can be concluded that Arabic language learning needs to be evaluated and improved, both in terms of teaching methods, learning media, and student learning motivation.